Asymmetric Information in Insurance Market: Evidence from the Automobile Insurance Market of Cyprus - Agathangelou, Leda (2008)
This research aims to highlight whether asymmetric information problem exists in Cyprus using as a sample the motor department's database of one of the biggest insurance companies of the island. By utilizing the existed literature that is work on adverse selection and moral hazard, my purpose is to test empirically whether the operational system used from Cypriot insurance companies is efficient in eliminating all residual asymmetric information. Knowing that the existence of the latter problems cause inefficiency in the insurance industry, I believe that it is very interesting to identify whether the insurance system in Cyprus works properly by managing to overcome these problems. Due to the fact that Cyprus is a very small country that recently joined European Union, there is no other research in the existed literature that tried to make the above tests. Therefore, is a necessity to give a lot of attention to the description of the country's insurance system in order to identify its discreteness. For the empirical part of this study, I used various econometric models that have been used from other researchers and I also made some unique tests that it was possible to be generated according with the data that I collected. Empirical tests revealed several contradictable conclusions. The first main part of the empirical analysis was concerning three different tests aiming to identify whether the choices of insured individuals were correlated with their risk type. In the second part, I made again some tests for the existence of correlation between the choices of policyholders and their risk type but using more homogeneous samples.